2006
DOI: 10.1080/02724980443000809
|View full text |Cite
|
Sign up to set email alerts
|

Programming strategies for rapid aiming movements under simple and choice reaction time conditions

Abstract: Increases in reaction time (RT) as a function of response complexity have been shown to differ between simple and choice RT tasks. Of interest in the present study was whether the influence of response complexity on RT depends on the extent to which movements are programmed in advance of movement initiation versus during execution (i.e., online). The task consisted of manual aiming movements to one or two targets (one- vs. two-element responses) under simple and choice RT conditions. The probe RT technique was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
55
2
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(69 citation statements)
references
References 33 publications
11
55
2
1
Order By: Relevance
“…Since target conditions were administered in blocks of trials in the present study, this finding is consistent with past research in which participants knew the number of targets in advance of stimulus presentation (Khan et al, 2006;2007;Klapp, 1995;2003). Also, reaction time increased as a function of the number of targets regardless of whether both segments were performed with the same or different hands and whether the second segment was in the same or opposite direction to the first.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Since target conditions were administered in blocks of trials in the present study, this finding is consistent with past research in which participants knew the number of targets in advance of stimulus presentation (Khan et al, 2006;2007;Klapp, 1995;2003). Also, reaction time increased as a function of the number of targets regardless of whether both segments were performed with the same or different hands and whether the second segment was in the same or opposite direction to the first.…”
Section: Discussionsupporting
confidence: 80%
“…This finding suggested that interference arising from the integration between segments occurs at a central Running Head: movement integration and the OTA level. In contrast to movements in which the second segment is in the same direction as the first, the one target movement time advantage does not emerge when the second movement involves a reversal in direction (Adam et al, 2000;Ketelaars, Garry, & Franks, 1997;Khan et al, 2006Khan et al, , 2007. This is because the antagonist activity of the first movement in a reversal sequence acts to decelerate the first segment and accelerate the second segment in the opposite direction.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Christina 1992;Fischman 1984;Klapp & Erwin 1976;Rosenbaum & Patashnik 1980;Quinn et al 1980;Klapp 1996;Khan et al 2006).…”
Section: Discussionunclassified
“…The basic finding of longer RT with increased movement complexity has been replicated by a large number of authors (e.g. Christina 1992;Fischman 1984;Klapp & Erwin 1976;Rosenbaum & Patashnik 1980;Sidaway, Sekiya & Fairbrother 1995;Quinn et al 1980;Klapp 1996;Khan et al 2006) although there is some debate over the precise factors that define movement complexity. Sidaway, Sekiya & Fairbrother (1995) and Lajoie & Franks (1997) found that RT increased when the size of a second target decreased in a serial aiming response (where two targets are contacted in a fixed order).…”
Section: Introductionmentioning
confidence: 93%